Le retour du Maroc à l’Union africaine - Frank Afom (Revue Internationale des Études du Développement, 2025)
This research discusses factors of Morocco’s return to African Union (AU) using policy brieves of Institut Amadeus, OCP Policy Center, and World Bank data. It suggests that the purpose to defend its interests related to the Western Sahara issue and the IOs membership privileges contributed to Morocco’s return to AU. By joining it, Morocco gave up its autonomy in order to curtail threats to its sovereignty in the Western Sahara and consolidate its economic integration into Africa: that assertion matches with a Machiavelli essential proposition: waiving a certain degree of autonomy (what is signifying one’s adhesion to an international institution as for a state), can be considered as the lesser harm when it is used for self-preservation motivations.